Evaluation of polyphenol content and antioxidant activity of the hydroalcoholic extract of Eisenia cokeri m.a. howe - Rodríguez, José E. (2019)
Was aimed to evaluate the content of total polyphenols and the antioxidant activity of the rhizoid, thallid and phyloid extracts of the Eisenia cokeri M.A. Howe. Using spectrophotometric reference methods. The content of total polyphenols was determined by the Folin-Ciocalteau method from the reference material Gallic acid and the antioxidant activity is referred to 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals and 2,2' -azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) ABTS.+. The results obtained showed that the content of total polyphenols is 3.111346 mg for the estípite; 0.4625 mg for the fronda and 2.31665 mg for the gallic acid rhizoid / 1 gram sample. For the antioxidant activity the extracts showed antioxidant activity in the DPPH methods for the rhizoid (IC50 = 659.74 μg / mL): for the fronda (IC50 = 280.00 μg / mL) and for the estípite (IC50 = 248, (IC50 = 20.3 μg / mL), and for the fronda (IC50 = 39.2 μg / mL) and for the estípite (IC50 = 50 μg / mL) 24.7 μg / mL). The obtained results show that the content of polyphenols is related very well to the antioxidant activity shown by the samples studied.